A risk management model applied to earthmoving projects - Rojas-Cazaluade, Oscar (2023)
This study provides a model for risk management applied to the projects of an earthmoving company to manage the causes of risk that threaten the achievement of the objectives in this type of project. This model helps to take the necessary measures to satisfy the promise of value demanded by the client and users and meet the commitments regarding cost, schedule, quality, and scope. Furthermore, this work applies the best risk management practices according to the methodology proposed by the Project Management Institute (PMI). The processes are applied in projects by earthmoving companies, such as planning, identification of risks, qualitative and quantitative analysis, planning and implementation of responses, and monitoring events.